Impact of baseline renal dysfunction on cardiac outcomes and end-stage renal disease in heart failure patients with mitral regurgitation: the COAPT trial. (3rd February 2022) - Beohar, Nirat; Ailawadi, Gorav; Kotinkaduwa, Lak N; Redfors, Björn; Simonato, Matheus; Zhang, Zixuan; Morgan, Loren Garrison; Escolar, Esteban; Kar, Saibal; Lim, David Scott; Mishell, Jacob M; Whisenant, Brian K; et al.
Abstract: Aims: Baseline renal dysfunction (RD) adversely impacts outcomes among patients with heart failure (HF) and severe secondary mitral regurgitation (MR). Heart failure and MR, in turn, accelerate progression to end-stage renal disease (ESRD), worsening prognosis. We sought to determine the impact of RD in HF patients with severe MR and the impact of transcatheter mitral valve repair (TMVr) on new-onset ESRD and the need for renal replacement therapy (RRT). Methods and results: The COAPT trial randomized 614 patients with HF and severe MR to MitraClip plus guideline-directed medical therapy (GDMT) vs. GDMT alone. Patients were stratified into three RD subgroups based on baseline estimated glomerular filtration rate (eGFR, mL/min/1.73 m 2 ): none (≥60), moderate (30–60), and severe (<30). End-stage renal disease was defined as eGFR <15 mL/min/1.73 m 2 or RRT. The 2-year rates of all-cause death or HF hospitalization (HFH), new-onset ESRD, and RRT according to RD and treatment were assessed. Baseline RD was present in 77.0% of patients, including 23.8% severe RD, 6.0% ESRD, and 5.2% RRT. Worse RD was associated with greater 2-year risk of death or HFH (none 45.3%; moderate 53.9%; severe 69.2%; P < 0.0001). MitraClip vs. GDMT alone improved outcomes regardless of RD ( P interaction = 0.62) and reduced new-onset ESRD [2.9 vs. 8.1%, hazard ratio (HR) 0.34, 95% confidence interval (CI) 0.15–0.76, P = 0.008] and the need for new RRT (2.5 vs. 7.4%, HR 0.33, 95% CI 0.14–0.78, P = 0.011). Conclusion: Baseline RD was common in the HF patients with severe MR enrolled in COAPT and strongly predicted 2-year death and HFH. MitraClip treatment reduced new-onset ESRD and the need for RRT, contributing to the improved prognosis after TMVr. Structured Graphical Abstract: Structured Graphical Abstract In the COAPT Trial, baseline renal dysfunction was common and strongly predicted 2-year death and heart failure hospitalization (HFH). However, treatment with the MitraClip was beneficial across all renal function groups in reducing the composite outcome of all-cause death and HFH (left). In addition, MitraClip treatment reduced incident end stage renal disease (top right) and the need for renal replacement therapy (bottom right).